IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS ENTREPRENEURSHIP DI PONDOK PESANTREN - Nasywa, Azka Aqilah; Mulyoto, M; Mulyo, Ahmad Mufrod Teguh (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
Character becomes something complex in social life that shows a person's good or bad personality. This study aims to find new theories about the Implementation of entrepreneurship-based character education at the Santri Manjung Wonogiri Islamic boarding school. The type of research used qualitative research with a descriptive approach. Data collection was carried out through in-depth interviews, participatory observation, and document review. The data that has been collected was analyzed using qualitative data analysis techniques. The results of this study are: (1) The Implementation of Entrepreneurship-based Character Education at the Santri Manjung Wonogiri Islamic Boarding School is to teach about independence is important for students to show their independence by showing how they can rely on their own abilities and take advantage of market opportunities to live. (2) Implementation of Entrepreneurship-based Character Education Needs to be Done at the Santri Manjung Wonogiri Islamic Boarding School because at the Santri Manjung Islamic boarding school, the idea of character education centered on entrepreneurship is a planned effort to provide independence and entrepreneurial skills to students in addition to their religious knowledge.